Moult strategies of Cory’s Shearwaters Calonectris diomedea borealis: The influence of colony location, sex and individual breeding status - Alonso, Hany Rafael de Drummond Ludovice Garcia (2009)
The replacement of old feathers is essential for birds, but it is also an energy-demanding task. As moult usually does not coincide with other stressful events in its annual cycle, such as reproduction and migration, the bird can optimise its use of time and energy allocated to different activities. There are very few studies comparing the moult strategies of populations with similar breeding calendars but occurring in areas of different habitat quality. Cory’s Shearwaters Calonectris diomedea have a partial moult–breeding overlap, an unusual phenomenon among pelagic seabirds. We have compared the moult schedules in Cory’s Shearwater colonies located in distinct environments (pelagic vs. coastal) and show that moult–breeding overlap is less extensive on Selvagem Grande, situated in deep oceanic waters, than on Berlenga, situated on the continental shelf. Colony attendance of failed breeders, most of which were moulting, was lower at Selvagem Grande than at Berlenga, which suggests that the feeding areas of birds from the former site are more distant from the colony. Failed breeders started to moult earlier than individuals still raising a chick, and breeding status had a stronger influence on determining the onset of wing-feather moult than colony location. Despite published evidence that internal circannual rhythms and external cues, such as variation in daylength, are important factors regulating moult schedules, it is clear that birds retain a considerable flexibility that allows them to respond to external factors in order to strategically manage time and energy in a way that is thought to maximise their fitness.